Knowledge, attitudes, and adherence relating to COVID-19 and its prevention measures in high-risk districts of Uganda in 2020 - Methodius, Tubihemukama; Musewa, Angella; Mirembe, Bernadette Basuta; Birungi, Doreen; Nitumusiima, Sarah; Naigaga, Irene; Kabasa, John David; Bazeyo, William (Frontiers in Epidemiology, 2023)
Introduction: COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There were no licensed vaccines and explicit medicines available for treatment at the time of conducting this study. Public health and social measures (PHSM) have been widely adopted to reduce transmission of COVID 19. Hence, assessing people’s knowledge, attitudes and adherence/practices related to COVID-19 management is crucial for identifying factors that may promote or hinder adherence to PHSM implementation. Methods: We conducted a cross sectional study in Amuru, Kyotera, Wakiso and Kampala districts of Uganda. We used simple random sampling technique to select households and conducted face to face interviews in selected households. We administered questionnaires to respondents to assess factors that promote or hinder adherence to and knowledge about PHSM implementation. We used a Likert scale to assess attitude among respondents towards COVID 19. Results: Out of the 270 respondents, 54(20%), 73(27%), 42 (15.6%) and 101(37.4%) were from Kampala, Amuru, Wakiso, and Kyotera districts respectively. Most of the respondents had adequate knowledge (72.2%), high level of adherence (63.7%) and about 57.8% of them had good attitudes relating to COVID-19 and its prevention measures. Inferential analysis revealed that people from Kampala district were at higher chances (Odds ratio = 4.668) of having high level of knowledge compared to people from Amuru district. It was also found that people with respondents who had high level of (adequate) knowledge were twice as likely to have good attitudes compared to those with low level of knowledge. In addition, People with good attitudes were 2.5 times as likely to adhere to the COVID-19 prevention measures as compared to those with poor attitude. Conclusion: Most respondents had limited knowledge although majority of them had adopted practices to prevent COVID 19. Respondents with low knowledge on COVID-19 need to be targeted, to improve their attitude and to adhere to safe practices